Preliminary study of freshwater mollusks in the mouth Station of the Rumaila River – Jableh – Lattakia - Syria - حمكو, ثناء; محمد قصاب ,; إقبال فاضل, (Latakia University Journal -Biological Sciences Series, 2023)
A freshwater medium, the mouth of the Rumaila River in the city of Jableh – Lattakia Governorate, was studied, where water and animal samples were collected. once a month for a year starting from 27/9/2021 to15/8/2022. The abiotic and biotic characteristics of the said medium have been studied. Fourteen species of mollusks have also been identified, of which thirteen belong to the class of Gastropoda, and six of which belong to under the row of the Prosobranchia, and seven of which belong to under the row of Pulmonata), and one species belongs to the class of Bivalvia. The physical and chemical qualities of the water of this plant have been studied as it shows that the water is of medium hardness. This plant has been distinguished by the higher percentage of chlorine electrolytes compared to the rest of the river, and the decrease in the amount of oxygen dissolved by water at the beginning of spring. It coincides with the high amount of oxygen consumed (COD) and this reflects the presence of organic pollution of human origin: Sewage.